Penerapan Pendidikan Karakter Siswa melalui Pembiasaan Membaca Asma’ul Husna di MAN 1 Metro - Adi Wijaya; Lutfi Fadilah (Yayasan Azhar Amanaa Yogyakarta, 2023)
This study aims to clearly explain the reality of the application of student character education through the habit of reading Asma'ul Husna at MAN 1 Metro. This type of research is a qualitative descriptive research field. The results of the data analysis showed that the application of character education for students through the habit of reading Asma'ul Husna at MAN 1 Metro is by exemplary, disciplined, and habituation methods in instilling religious, honest, disciplined, hard-working, creative, environmental-friendly characters, and Responsibility. Then the supporting factors in the application of character education are economic factors, internal factors such as the family environment, and teachers. While the factors that hinder the implementation of character education are the lack of attention and cooperation between parents and the school. Therefore it is necessary to hold parenting to unify the understanding between parents of students and the school regarding the goals or vision and mission of the school so that they can jointly supervise and educate the character of these students.